Retrospective study of cesarean rate in a tertiary care hospital - Kabbur, Vasant; S., Lakshmi K.; Umadi, M. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Worldwide there has been an increase in the rate of caesarean delivery due to multiple factors. The main objective of this study is to analyze the various indications of caesarean delivery over a period of 4 years and to evaluate the maternal and fetal outcomes between elective and emergency caesarean section. Methods: Retrospective study conducted at the Department of Obstetrics and Gynecology, Belgaum Institute of Medical Sciences, Belagavi, India. The study period was from January 2016 - December 2017. The details were taken from case sheets, operation and parturition records and newborn records of 325 patients who underwent caesarean section. The data was analyzed with special reference to the indication of caesarean section, maternal and fetal outcomes among elective and emergency cases. Results: The incidence of cesarean section was 28%. The commonest indication for C-delivery was repeat cesarean (43%) followed by CPD (15%). Failed induction and Fetal distress were the next common indication (10%) and (7%) respectively. Maternal morbidity was 20% with 1 maternal death (0.1%). The commonest complications were primary hemorrhage and wound infection, intra OP and post OP respectively. The perinatal morbidity and mortality were 10% and 2.26% respectively. Conclusions: The incidence of ceaserean section is 12.5% in our hospital falling well within the WHO guidelines. Among the indications, previous LSCS is contributing to a greater percentage, which should be reduced by promoting more VBAC. It also emphasizes the need for reducing primary sections. Post-partum haemorrhage has been brought well under control, sepsis still accounts for greater postop morbidity and meconium aspiration is the commonest cause for perinatal morbidity and mortality.